Neuroprotective role of Melatonin against aluminum-induced oxidative stress in the hippocampus of mouse brain - N. John Sushma, S. Priyanka, K. Jayantha Rao (Journal of Applied Pharmaceutical Science)
We evaluated the effect of melatonin (Mel) in male albino mice which received aluminum acetate (Al) for 6 weeks (3.5 mg/kg body weight) (b.w.) i.p. five times per week. Moreover mice received Mel (7mg/kg b.w.i.p. 5 days/week) for 6 weeks. At the end of the treatment hippocampus was removed and processed to examine the oxidative stress markers. Following Al exposure oxidative stress increased significantly, estimated by increased thiobarbituric acid reactive substances (TBARS) and decrease in the activity of antioxidant enzymes (superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), reduced glutathione (GSH),glutathione peroxidase (GPx) and glutathione-s-transferase (GST). Al+Mel treatment significantly prevented the aluminum induced decrease in antioxidant enzymes as well as decrease in TBARS. Histopathological evidence in the hippocampi revealed the protective effect of melatonin against Al induced damage in light and transmission electron microscopic (TEM) studies. These results supported that melatonin suppresses the oxidative stress. This may result from the higher efficacy of melatonin in scavenging various free radicals and also because of its ability in stimulating the anti oxidant enzymes.
Keywords: Aluminum, Hippocampus, Oxidative stress, Melatonin.